Custody of children in domestic violence cases / Afi Afifah Razali...[et al] - Razali, Afi Afifah; Zainol, Nurul Husna; Mahadzir, Nur Zulaikha; Md Zahidi, Siti Nurani (Faculty of Law, 2013)
This research traces the custodial status of child victim in domestic violence cases. The focus is on protecting the interest of the chid victim by ensuring that the statutory provisions dealing with the issue of domestic violence in Malaysia are sufficient to protect the child victim. The statutory provisions that have been considered include the Malaysian Domestic Act 1994 (DVA), the Malaysian Child Act 2001 (CA), the Guardianship of Infants Act 1961 (GIA), and the Law Reform of (Marriage and Divorce) Act 1976 (LRA). Comparison was made between four situations in domestic violence cases where the issue of custody of the child victim might arise. The first situation concerns on the custodial status of the child victim when both parents are abusive. The second situation concerns on the custodial status during the continuance of the period of IPO. The third situation is when domestic violence leads to the divorce of the parents. The fourth situation is when domestic violence happened but there was no divorce between the parents. Until today, there is no specific provision made in relation to the custody of the child victim in domestic violence cases. Thus this research will discuss the issue on the custodial status of the child victim in such cases in order to provide a better protection for the children.